Clinicopathologic predictors of incomplete excision after loop electrosurgical excision for cervical preneoplasia. - Kietpeerakool C. (2014)
The aim of this study was to identify the factors affecting incomplete excision after the loop electrosurgical excision procedure (LEEP) for evaluation and treatment of cervical neoplasia. Patients with abnormal cervical cytology who underwent colposcopy and LEEP at Chiang Mai University Hospital between October 2004 and July 2005, were retrospectively evaluated. During the study period, 201 patients were eligible for analysis. All cone margin involvement was observed in 44% of the patients (95% CI, 37.3-51.4). Multivariate analysis revealed that invasive cancer on cytology (adjusted odds ratio [aOR] =3.05, 95% confidence interval [CI] =1.03 to 9.00; P=0.02), invasive cancer on LEEP histopathology (aOR=9.73, 95%CI =3.95 to 23.9; P<0.001), and a cone length of less than 10 mm (aOR =1.95, 95%CI =1.04 to 3.66; P =0.03) were significant predictors for any cone margin involvement. For endocervical margin involvement, postmenopausal status and a cone length of less than 10 mm were significant predictors of incomplete excision. In contrast to endocervical margin involvement, postmenopausal status was significantly associated with a decreased risk of ectocervical margin involvement. Invasive cancer on histopathology was a significant predictor of both ecto- and endocervical margin involvement. In conclusion, invasive cancer either on cytology or LEEP specimens and a cone length of less than 10 mm are significant predictors of incomplete excision.